Modeling of heat transfer distribution in tumor breast cancer during microwave ablation therapy. Issue 8 (30th April 2022) - Selmi, Marwa; Iqbal, Amjad; Smida, Amor; Waly, Mohamed Ibrahim; Belmabrouk, Hafedh
Abstract: Microwave (MW) ablation is a strong tool that has been used in clinical therapy for numerous cancer tumors. This method takes advantage of the heat from MW energy produced by an antenna to destroy cancer cells without causing damage to the healthy tissue. This technique's efficiency is correlated to the temperature reached during the MW process. The antenna immersed in a tissue radiates a power that heats the living tissue, that is, the cancer cells and their environment. The administered power leads to a temperature increase that should attain a particular level to enable the killing of the dangerous cancer cells. On the other hand, it should not exceed another level to preserve healthy cells. Bioheat and electromagnetic equations are used to model the thermal ablation process. The finite element method is used to solve the governing equations used to model the process. This article is devoted to studying the influence of the type of antenna on the temperature distribution in the breast tissue, the specific absorption rate (SAR), and the amount of the necrotic tissue. Two configurations have been investigated, namely, a single‐ or a double‐slot antenna. The obtained results reveal that the temperature, SAR, and the fraction of necrotic of the breast tissue are higher when a single‐slot antenna is used. In addition, the input MW power has an important effect on the results. Some precautions should be taken in advance to prevent the temperature from rising to 50°C, which may induce damage to healthy cells.